Pengaruh Pengungkapan Informasi Keuangan Melalui Situs Web Perusahaan Terhadap Nilai Perusahaan - Mutiara Tresna Parasetya; Bayu Kurniawan (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2021)
The purpose of this study is to examine the effect of financial information and stock information disclosure through the company’s website on firm’s value (stock price). This study uses multiple regression analysis to examine the effect of financial information disclosure and stock information disclosure through the website on firm’s value. This study also uses the classic assumption analysis to fulfil the multiple regression analysis. Sample in this paper is companies listed in Bursa Efek Indonesia with sub sector bank. This study found that there was no influence between financial information disclosure through the company’s website on firm’s value. This study also found that there was no effect of stock information disclosure through the company’s website on firm’s value.